4(C-9)C=15

Simple and best practice solution for 4(C-9)C=15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(C-9)C=15 equation:


Simplifying
4(C + -9) * C = 15

Reorder the terms:
4(-9 + C) * C = 15

Reorder the terms for easier multiplication:
4C(-9 + C) = 15
(-9 * 4C + C * 4C) = 15
(-36C + 4C2) = 15

Solving
-36C + 4C2 = 15

Solving for variable 'C'.

Reorder the terms:
-15 + -36C + 4C2 = 15 + -15

Combine like terms: 15 + -15 = 0
-15 + -36C + 4C2 = 0

Begin completing the square.  Divide all terms by
4 the coefficient of the squared term: 

Divide each side by '4'.
-3.75 + -9C + C2 = 0

Move the constant term to the right:

Add '3.75' to each side of the equation.
-3.75 + -9C + 3.75 + C2 = 0 + 3.75

Reorder the terms:
-3.75 + 3.75 + -9C + C2 = 0 + 3.75

Combine like terms: -3.75 + 3.75 = 0.00
0.00 + -9C + C2 = 0 + 3.75
-9C + C2 = 0 + 3.75

Combine like terms: 0 + 3.75 = 3.75
-9C + C2 = 3.75

The C term is -9C.  Take half its coefficient (-4.5).
Square it (20.25) and add it to both sides.

Add '20.25' to each side of the equation.
-9C + 20.25 + C2 = 3.75 + 20.25

Reorder the terms:
20.25 + -9C + C2 = 3.75 + 20.25

Combine like terms: 3.75 + 20.25 = 24
20.25 + -9C + C2 = 24

Factor a perfect square on the left side:
(C + -4.5)(C + -4.5) = 24

Calculate the square root of the right side: 4.898979486

Break this problem into two subproblems by setting 
(C + -4.5) equal to 4.898979486 and -4.898979486.

Subproblem 1

C + -4.5 = 4.898979486 Simplifying C + -4.5 = 4.898979486 Reorder the terms: -4.5 + C = 4.898979486 Solving -4.5 + C = 4.898979486 Solving for variable 'C'. Move all terms containing C to the left, all other terms to the right. Add '4.5' to each side of the equation. -4.5 + 4.5 + C = 4.898979486 + 4.5 Combine like terms: -4.5 + 4.5 = 0.0 0.0 + C = 4.898979486 + 4.5 C = 4.898979486 + 4.5 Combine like terms: 4.898979486 + 4.5 = 9.398979486 C = 9.398979486 Simplifying C = 9.398979486

Subproblem 2

C + -4.5 = -4.898979486 Simplifying C + -4.5 = -4.898979486 Reorder the terms: -4.5 + C = -4.898979486 Solving -4.5 + C = -4.898979486 Solving for variable 'C'. Move all terms containing C to the left, all other terms to the right. Add '4.5' to each side of the equation. -4.5 + 4.5 + C = -4.898979486 + 4.5 Combine like terms: -4.5 + 4.5 = 0.0 0.0 + C = -4.898979486 + 4.5 C = -4.898979486 + 4.5 Combine like terms: -4.898979486 + 4.5 = -0.398979486 C = -0.398979486 Simplifying C = -0.398979486

Solution

The solution to the problem is based on the solutions from the subproblems. C = {9.398979486, -0.398979486}

See similar equations:

| 31=p-91 | | k*k=36 | | 40*2=r | | 3x-3=1+2x | | x*-10(x-1)=-11 | | 3x-3=9-6x | | 9x^2+3x-50=0 | | 90+0.1x=100 | | 90+0.1x=95 | | a+5=5 | | 99+0.1x=90 | | c-14=6 | | 6(10x-13)=222 | | -12/3x-41/7 | | 16-s=20 | | -6+w/3=-8 | | -36=p-01 | | 4a-4=-2 | | 5/1211/18 | | 3x^4-6x^3+3x^2=0 | | x(6-4)+3=15 | | f(m+3)=2m^2-2m+1 | | (3x+7)(x+5)=0 | | f=-18+-10x | | 16u^7x^6-7u^2x^6/-4u^3x^4 | | (x^2-3x+4)(2x-1)=0 | | f=-17+5x-1+-15x | | y/3+y | | 8-m=20 | | 15x^2y^3/25x^5y^3 | | 21x-14/4=-14 | | 1/2y+y |

Equations solver categories